#TITLE_ALTERNATIVE# - GHUFRON (NIM: 12012025), MUHAMMAD
The planning tunnel is located on the road Tawaeli-Toboli. Tawaeli-Toboli road as a national road that has trails winding and one attempt to cut the travel time that by tunnel. The tunnel will break through metamorphic rocks, so needs rock mass classification to determine the design of support. The research is located in the Tanantovea area, Donggala Regency, and Parigi Utara area, Parigi Moutong regency, Central Sulawesi. Geographically, Tanantovea located at 0°43’32.5’’ LS, 120°00'49.5’’ BT and Parigi Utara is located at 0°43’25.1’’ LS, 120°01’12.6’’ BT. Geologically, the area of research included in the Metamorphic rocks complex of Sulawesi. The result of petrographic observation, the lithology are actinolite schist and biotite gneiss. Tunnel has a length of 640 m with a width of 10 m and a height of 10 m. Rock masses in the research sites are analyzed using Rock Mass Rating (RMR) and System Q. Based on the results of calculations using the method of RMR, a rating of rock mass on the location of SC 1, SC 3, and SC 4 are included in the classification II (good rock) and SC 2 is in classification III (fair rock). The results of method Q system is in locations SC 1, SC 3, and SC 4 are classified as poor and SC 2 is in classification as very poor. Determination of support design in classification II (good rock) such as rock bolts with a length of 3 m and the spacing between bolts 2.5 m, wire mesh and shotcrete with a thickness of 50 mm on the top of the tunnel and the classification III (fair rock) support design such as rock bolts with a length of 4 m and the spacing between bolts 1.5-2 m in the upper part and the tunnel wall and shotcrete with a thickness of 50-100 mm thick at the top and 30 mm on the walls of the tunnel. Meanwhile, the results of the method Q System at SC 1, SC 3 and SC 4 are in the category poor and SC 2 is in the category very poor. Support design based on Q System, SC 1, SC 3, and SC 4 such as fiber shotcrete with a thickness 60-90 mm, rock bolts with a length of 3.5 m, and the spacing between bolts 2.5 m and SC 2 has support such as fiber shotcrete with a thickness 90-120 mm, rock bolts with a lenght of 3.5 m, and the spacing between bolts 2.1-2.5 m.